FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN SOFTWARE BAJAKAN DI KALANGAN MAHASISWA - Mardalis, Ahmad; S., Dharma Putra (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this research is to determine what are the factors that led to the use ofpirated software among students. To determine the relationship of using pirated software amongstudents views by consumer characteristics included age, sex, and spending each month.Thepopulation in this study were students who use pirated software. Sampling was done with accidentalSampling. Samples taken in this study were students who use pirated software or software thathappens to be found in the current study sample and the samples taken in this study as many as100 people. Since this amount exceeded the minimum sample of 96 people. Based on data analysishas been done, the writer can conclude: Factors attitude and motivation factors are factors thatinfluence the use of pirated software among students who are able to explain 30,189% and 18,416%.For variable attitudes by age and sex have nothing to do with piracy committed by students. If byspending a month it has to do with piracy committed among students. For motivation variablebased on the characteristics of age and sex have nothing to do with piracy committed by students.If based on the characteristics of spending per month it has to do with piracy committed amongstudents.